PHS Guideline for Reducing Human Immunodeficiency Virus, Hepatitis B Virus, and Hepatitis C Virus Transmission Through Organ Transplantation - Seem, Debbie L.; Lee, Ingi; Umscheid, Craig A.; Kuehnert, Matthew J. (Public health reports (1974), 2013)
Seem et al examine data addressing 10 key questions within five major topic areas to evaluate the evidence on reducing transmission of HIV, hepatitis B virus, and hepatitis C virus through organ transplantation. They draw upon subject-matter experts to draft summaries related to these questions, as a preliminary scan of the literature showed that a systematic review would likely yield insufficient data. Recommendations related to the 10 key questions were based on a targeted systematic review of the best available evidence, with explicit links between the evidence and recommendations. To accomplish this review, they use a modified Grading of Recommendations, Assessment, Development, and Evaluation approach for evaluating quality of evidence and determining strength of recommendations.